Study of the nature of the particle distribution coefficient function in the boundary layer of the sand cloud - GUERGAB, Amer; ZONBOUT, Abou Baker; Hadj Aissa, Aissa (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2024)
NOTE: PLACE YOUR OWN LICENSE HERE This sample license is provided for informational purposes only. NON-EXCLUSIVE DISTRIBUTION LICENSE By signing and submitting this license, you (the author(s) or copyright owner) grants to DSpace University (DSU) the non-exclusive right to reproduce, translate (as defined below), and/or distribute your submission (including the abstract) worldwide in print and electronic format and in any medium, including but not limited to audio or video. You agree that DSU may, without changing the content, translate the submission to any medium or format for the purpose of preservation. You also agree that DSU may keep more than one copy of this submission for purposes of security, back-up and preservation. You represent that the submission is your original work, and that you have the right to grant the rights contained in this license. You also represent that your submission does not, to the best of your knowledge, infringe upon anyone's copyright. If the submission contains material for which you do not hold copyright, you represent that you have obtained the unrestricted permission of the copyright owner to grant DSU the rights required by this license, and that such third-party owned material is clearly identified and acknowledged within the text or content of the submission. IF THE SUBMISSION IS BASED UPON WORK THAT HAS BEEN SPONSORED OR SUPPORTED BY AN AGENCY OR ORGANIZATION OTHER THAN DSU, YOU REPRESENT THAT YOU HAVE FULFILLED ANY RIGHT OF REVIEW OR OTHER OBLIGATIONS REQUIRED BY SUCH CONTRACT OR AGREEMENT. DSU will clearly identify your name(s) as the author(s) or owner(s) of the submission, and will not make any alteration, other than as allowed by this license, to your submission.
Energetic Mechanics